Dinamika Hukum Perdata dalam Pembayaran Cicilan Dengan Tinjauan Terhadap Sistem Beli Sekarang, Bayar Nanti (Pay Later) - Dewantara Bagus Pamungkas (CV. Lenggogeni Data Publishing, 2023)
Short-term financing, especially through the Buy Now, Pay Later (BNPL) system, is an interesting phenomenon in the dynamics of civil law. This literature study describes the legal aspects involved in the installment payment process involving consumers, service providers and merchants. In relation to consumers, legal literature highlights the legal protection provided to consumer rights and obligations in BNPL transactions. The concept of contractual responsibility and consumer protection is an important focus, considering the involvement of third parties (service providers) in these transactions. It is also important to understand merchant involvement in BNPL systems. Literature analysis reveals aspects of civil law between traders and consumers, especially in the context of installment payment risks. The involvement of third parties in the payment process creates legal dynamics that need to be addressed, including the merchant's responsibilities towards the service provider. Additionally, the literature provides insight into the legal implications related to establishing terms and conditions in BNPL contracts. The availability of clear and transparent information is key in maintaining civil law between consumers, service providers and traders. Overall, this literature study illustrates the complexity of civil law dynamics in the context of installment payments through the BNPL system. Consumer protection, third party involvement, and merchant obligations are crucial elements that need to be considered to maintain integrity and fairness in these transactions. Abstrak Pembiayaan jangka pendek, khususnya melalui sistem Beli Sekarang, Bayar Nanti (BNPL), menjadi fenomena menarik dalam dinamika hukum perdata. Studi pustaka ini menguraikan aspek-aspek hukum yang terlibat dalam proses pembayaran cicilan yang melibatkan konsumen, penyedia layanan, dan pedagang. Dalam kaitannya dengan konsumen, literatur hukum menyoroti perlindungan hukum yang diberikan terhadap hak dan kewajiban konsumen dalam transaksi BNPL. Konsep tanggung jawab kontraktual dan perlindungan konsumen menjadi fokus penting, mengingat adanya keterlibatan pihak ketiga (penyedia layanan) dalam transaksi ini. Penting juga untuk memahami keterlibatan pedagang dalam sistem BNPL. Analisis literatur mengungkapkan aspek hukum perdata antara pedagang dan konsumen, terutama dalam konteks risiko pembayaran cicilan. Keterlibatan pihak ketiga dalam proses pembayaran menciptakan dinamika hukum yang perlu diatasi, termasuk tanggung jawab pedagang terhadap penyedia layanan. Selain itu, literatur memberikan wawasan tentang implikasi hukum terkait penetapan syarat dan ketentuan dalam kontrak BNPL. Ketersediaan informasi yang jelas dan transparan menjadi kunci dalam menjaga keabsahan perdata antara konsumen, penyedia layanan, dan pedagang. Secara keseluruhan, studi pustaka ini menggambarkan kompleksitas dinamika hukum perdata dalam konteks pembayaran cicilan melalui sistem BNPL. Perlindungan konsumen, keterlibatan pihak ketiga, dan kewajiban pedagang menjadi elemen-elemen krusial yang perlu diperhatikan untuk menjaga integritas dan keadilan dalam transaksi ini. Kata Kunci: BNPL, Perdata, Konsumen, Pedagang, Perlindungan Hukum.